2020
DOI: 10.15252/emmm.201911248
|View full text |Cite
|
Sign up to set email alerts
|

A high‐affinity, bivalent PDZ domain inhibitor complexes PICK 1 to alleviate neuropathic pain

Abstract: Maladaptive plasticity involving increased expression of AMPAtype glutamate receptors is involved in several pathologies, including neuropathic pain, but direct inhibition of AMPARs is associated with side effects. As an alternative, we developed a cell-permeable, high-affinity (~2 nM) peptide inhibitor, Tat-P 4 -(C5) 2 , of the PDZ domain protein PICK1 to interfere with increased AMPAR expression. The affinity is obtained partly from the Tat peptide and partly from the bivalency of the PDZ motif, engaging PDZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 94 publications
2
28
0
Order By: Relevance
“…In good agreement with theory we showed that the retention time and equilibration time becomes extremely long (t 1/2 , ~ 375 min, k on,av ~ 25 min at a concentration of 5 times K av ) (Erlendsson et al, 2019 ). From this insight, a high avidity bivalent inhibitor of PICK has recently been developed that alleviate neuropathic pain in rats (Christensen et al, 2020 ).…”
Section: Intracellular Aviditymentioning
confidence: 99%
See 1 more Smart Citation
“…In good agreement with theory we showed that the retention time and equilibration time becomes extremely long (t 1/2 , ~ 375 min, k on,av ~ 25 min at a concentration of 5 times K av ) (Erlendsson et al, 2019 ). From this insight, a high avidity bivalent inhibitor of PICK has recently been developed that alleviate neuropathic pain in rats (Christensen et al, 2020 ).…”
Section: Intracellular Aviditymentioning
confidence: 99%
“…In addition to the effects we have described in this review, multivalency may also lead to a series of other properties not observed for monovalent protein-ligand complexes. Designing multivalent drugs have huge potential and is already widely applied (Mourez et al, 2001 ; Kim et al, 2008 ; Bach et al, 2012 ; Dubacheva et al, 2015 ; Karlsson et al, 2015 ; Maric et al, 2015 ; Einav et al, 2019 ; Christensen et al, 2020 ; Ortega et al, 2020 ). Within the past 5 years it has become increasingly clear how multivalent interactions of particularly RNA and IDP's drive liquid-liquid phase separations (Cohan and Pappu, 2020 ; Conicella et al, 2020 ; Guillén-Boixet et al, 2020 ; Martin et al, 2020 ; Ryan et al, 2020 ).…”
Section: Emerging Concepts and Future Perspectivesmentioning
confidence: 99%
“…A recent work reports a small molecule inhibitor, Tat-P 4 -(C5) 2 , with both strong affinity and specificity to the PICK1 PDZ domain. 30 Furthermore, Tat-P 4 -(C5) 2 demonstrates efficacy in reducing addiction-like behavior in mice. 75 Tat-P 4 -(C5) 2 interacts with the binding pocket of the PDZ domain as well as negatively charged residues on of β B- β C loop which introduces an additional layer of stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…2629 A recent work by Christensen et al shed light on a drug which can partially reduce the biological function of PICK1. 30 In parallel, computational groups have aided this effort by performing molecular dynamics (MD) simulations to reveal intradomain interactions of other PDZ domains and PDZ-ligand interactions. 29,3144 Furthermore, some efforts have been put towards understanding the structural and energetic allosterism of PDZ domains overall.…”
Section: Introductionmentioning
confidence: 99%
“…A significant fraction of PPIs is dependent on short linear peptides, which are increasingly recognized for their roles in signaling and regulatory networks ( Pawson and Nash, 2003 ) and antibody/antigen recognition ( Brennan et al., 2010 ). Thus, they provide opportunities for therapeutic intervention and valuable starting points for the development of immunological biopharmaceuticals ( Fosgerau and Hoffmann, 2015 ) and the design of PPI modulators ( Christensen et al., 2020 ). Widely applied methods for the characterization and affinity determination of PPIs include peptide and protein microarrays ( Lyamichev et al., 2017 ; Templin et al., 2002 ), surface plasmon resonance (SPR) ( Patching, 2014 ), biolayer interferometry (BLI) ( Sultana and Lee, 2015 ), isothermal calorimetry (ITC) ( Ye and Wu, 2000 ), fluorescence polarization (FP) ( Rooklin et al., 2017 ), and microscale thermophoresis (MST) ( Duhr and Braun, 2006 ; Wienken et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%